The system of cumulative marking in mathematics studies: advantages and disadvantages - Griniuvienė, Liucija; Naudžiūnienė, Vanda (Lietuvos matematikos rinkinys, 2003)
The analysis of the questionnaire data obtained in the Faculty of mathematics and informatics of Vilnius Pedagogical University is presented. The analysis covers a four-year period of the cumulative system application.